The Abundance and Diversity of Plankton in Cidurian River Ecosystem, Bandung, West Java - Yuliyana, Adika; Pribadi, Tri Dewi Kusumaningrum (BIOVALENTIA: Biological Research Journal, 2025)
River pollution is a special concern in environmental studies due to human waste disposal, while the rivers are still the main source for anthropogenic activities of the community. Population growth in Bandung City (2.26% annually) has intensified these activities, contributing to water pollution in the Cidurian River, a vital 24.86 km waterway in West Java. Improper waste management and agricultural runoff have further degraded water quality, affecting aquatic life, including plankton. This study was conducted to analyze the abundance and diversity of plankton as aquatic bioindicators in the Cidurian River. Sampling was conducted at four stations consisting of nine plots selected based on purposive sampling method with three repetitions. The results revealed 26 species of phytoplankton and 11 species of zooplankton. The highest abundance of phytoplankton and zooplankton was found at station 1, with values of 130 cells/L and 56 individuals/L respectively. Chlorophyceae was the most frequently observed class at all stations. Ecological analysis using the Shannon-Wiener Diversity Index showed the highest values at station 1, with phytoplankton H’=2.21 and zooplankton H’=0.79, while the lowest species dominance was observed at stations 3 and 4. Environmental parameters indicated variations among stations. Based on the data, the water quality of the Cidurian